POLA MIKROORGANISME PADA LIANG VAGINA WANITA HAMIL DI RSU DR. SOETOMO SURABAYA - Sianny Herawati; M.Y. Probohoesodo; Prihatini . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
In pregnant women especially in the third trimester, it is seldom that attention is paid to microorganism in the vagina. Many studies have reported about microorganism in the vagina which possibly can infect the foetus. This is due to the migration of bacterial colonization in the vagina to the foetus during labour, causing infection or sepsis in the foetus after delivery. To study the microorganism pattern in the vagina of pregnant women, pathogenic as well as normal flora of the vagina. If the microorganism is known, prevention or treatment before and after delivery can be applied. Population was recruited from pregnant women in the third trimester who visited The Maternity Outpatient Clinic, Dr. Soetomo Hospital from September until October 2005. Specimens from ostium of the cervix and posterior fornix of the vagina were collected in Amies media and examined in the Department of Clinical Pathology, Airlangga University/ Dr. Soetomo Hospital to detect any bacteria, fungi and parasites using direct method and culture. The microorganism pattern from 30 pregnant women consisted of non-haemolytic Streptococcus 25%, Escherichia coli 25%, Lactobacillus 35%, Staphylococcus aureus 10%, and Staphylococcus coagulase negative 5%. The result of fungi examination showed 14 (47%) samples with negative result and 16 (53%) samples with positive result (Candida sp). The pattern of microorganism was dominated by Lactobacillus and Candida sp but no parasites in the vagina were found.